Percepatan Waktu Pelaksanaan Pembangunan Gedung Rumah Sakit Aisyiyah Kabupaten Ponorogo Menggunakan Metode PERT (Program Evaluation and Review Technique) - Ilham Juniar Abraham; Ahmad Ridwan; Suwarno Suwarno (Faculty of Engineering, Kadiri University, 2022)
Project scheduling is one of the important factors for successful project implementation that can be achieved in accordance with the initial planning. Problems that can hinder project management are limited resources, inaccurate reports and costly and costly. The delay in the completion of the project itself is a very undesirable condition, because it can harm both parties both in terms of time or cost. The purpose of this study is to determine the probability of accelerating the implementation time from the period obtained by taking into account the critical path and calculation of cost crashing in the Aisyiyah Ponorogo Hospital construction project. The research method used in this study was to analyze the time schedule in the RAB by comparing the project schedule using the PERT (Program Evaluation and Review Technique) method. The data used is the duration of the project time to obtain critical trajectory results, standards and variances. The results of the scheduling analysis with the PERT method obtained a critical path with B-C-D-E-L-M with an acceleration of the implementation time of project activities for 49 weeks on the critical path and a non-critical path for 79 weeks from the planned time. buildings can speed up implementation time by a possible percentage of 92,073% with efficient calculation of crashing costs with the addition of working hours/overtime at a duration of 49 weeks rather than having to increase labor to achieve this probability.